An Unusual Presentation of Adult-Onset Still’s Disease as Hemophagocytic Lymphohistiocytosis in a Male Patient - Kuruvilla, Neenu (Cureus, 2020)
Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and potentially fatal condition characterized by immune activation and multi-organ dysfunction. HLH can be inherited in an autosomal recessive fashion, but can also be secondary to infections, malignancy, immunosuppression, and autoimmune conditions. Adult-onset Still’s disease (AOSD) is an autoimmune disorder that can predispose patients to HLH. AOSD, similar to other autoimmune conditions, is more common in females than males. However, the occurrence of AOSD in males and subsequent predisposition to HLH is rarely reported. We report the case of a 23-year-old male patient who presented with fever, joint pain, and rash for 20 days. On evaluation, he fulfilled the diagnostic criteria for AOSD and HLH, and a diagnosis of HLH secondary to AOSD was made. He was treated with pulse dose steroids and gradually tapered. AOSD and HLH have overlapping clinical and laboratory features and hence their co-occurrence poses diagnostic challenges. The mortality rate of HLH is high and hence prompt initiation of treatment is of utmost importance.